An assessment of a 'training-of-trainers programme for clinic committees' in a South African district: a qualitative exploratory study - Natasha Esau; René English; Maylene Shung-King (BMC, 2020)
Abstract Background In South Africa (SA), clinics and community health centres are the predominant primary level health care facilities in the public health sector. As part of legislated health governance requirements, clinic committees (referring to those for clinics and community health centres) were established to provide management oversight and bring to bear the perspectives and participation of communities at Primary Health Care (PHC) facilities. Clinic committees need training in order to better understand their roles. Facilitators in a district of SA were trained through a designated programme, called the 'PHC Facility Governance Structures Trainer-of-Facilitator (ToF) Learning Programme', in preparation for the training of clinic committees. This paper explores how the programme had evolved and was experienced by the trained facilitators, in a district in SA. Methods We employed a retrospective qualitative case study design, guided by the Illuminative Evaluation Framework, with the training programme in the selected district as the case. The study assessed whether the intended aims of the training programme were clearly conveyed by the trainers, and how participants understood and subsequently conveyed the training programme intentions to the clinic committees. Key informant interviews and focus group discussions were conducted with trainers and managers, complemented by a review of relevant policy and legislative documents, and published literature. Study participants were purposively selected based on their involvement in the development, facilitation or training of the programme. Thirteen individuals participated in the study, and 23 (national, provincial and partner) documents were reviewed. Results Despite the different perceptions and understandings of the ToF Learning Programme, its overall aims were achieved. Trainers' capacity was strengthened and clinic committees were trained accordingly. The training programme holds promise for possible national scale-up. The high quality of the interactive posters can be considered equally valuable as a training tool as the training manuals. Conclusions Trainers' capacity was strengthened and clinic committees were trained accordingly, despite deviations in implementation of the original training approach and plan.